A Good Life: Friendship, Art and Truth - Nehamas, Alexander; Vertzagia, Despina; Georgakopoulou, Triseugeni; Pavlidou, Jenny; Plevridi, Katerina; Stamos, Fotis (Conatus - Journal of Philosophy, 2018)
In September 2017 Alexander Nehamas kindly accepted our invitation to have a meeting in Athens in order to discuss several issues of philosophical interest; with his latest publication On Friendship (New York: Basic Books, 2016) as a starting point we soon moved over to a multitude of topics Nehamas has so far dealt with. The whole conversation spirals around the probably most challenging and demanding issue as far as practical philosophy is concerned – yet one every moral agent needs to provide an adequate answer to during his lifetime: Values. Do they exclusively belong to the domain of morality? Nehamas claims that “although moral values […] are important […], they are not the only values that determine whether a life is or is not worthwhile”. This view inevitably shifts the focus from individual values - even fundamental ones such as friendship, art and truth- to the real issue: What is a good life, after all?